Implications of telemedicine and health policy: An examination of facilitators and barriers through a systematic review (2020)
Background: Telemedicine diagnoses and treats patients remotely via telecommunications technology all over the world. Telemedicine becomes more prevalent as providers recognize the benefits, patients receive increased access and payers see the reduction in cost of care. Objective: Telemedicine studies have shown success in limiting geographical constraints, time spent, and costs incurred by patients with positive health outcomes across medical specialties. The aim of this review is to evaluate the implications of telemedicine and health policies. Methods: An assessment of the literature in four databases was made on content germane to health policy implications of telemedicine. From the results of the search, 48 publications were kept for analysis. Results: The fifteen facilitators mentioned most often were increased access, increased convenience, improved population health, care enabled through mobile technology, self-efficacy, increased patient-toprovider communication, cost advantages, efficacy of modality, increased health outcomes, reaches developing countries, increased quality, a positive previous experience, and a secure means of care. The twelve barriers mentioned most often were the increased cost to providers, patient privacy, technical literacy, state licensing, data security, socioeconomics, limited reimbursements, issues of interoperability, patient safety, less personal means of care, misaligned incentives, and ethical concerns. Conclusions: Telemedicine has the potential for growth and adoption, however, there are several implications and barriers of health policy surrounding telemedicine that make it difficult to adopt. Policies will likely encourage and incentivize its spread and use. Future research should focus on standardization of telemedicine and new policies and incentives that encourage its use.